OPTIMALISASI PAJAK DAERAH DALAM RANGKA MENINGKATKAN KEMAMPUAN KEUANGAN DAERAH (STUDI PENELITIAN DI PEMERINTAH KOTA SEMARANG) - Supratiwi, Nunik Retno Herawati (JURNAL ILMU SOSIAL, 2013)
PAD demands greater increased as more and more authority delegated to local government that accompanied the transfer of personnel, equipment, financing, and documentation to the area in large numbers. Equalization funds from the center would not be a mainstay continuously. With revenues expected dependence on the central area is reduced. In this regard, optimization of local revenue sources were necessary to increase the ability of local finance. It required the intensification of the subjct and the object of revenue.In connection with the above problems, this study analyzed the local tax identification and Semarang City government as one of its sources of revenue. In identifying who would do it, researchers would analyze the local tax which was not optimal so that still needs to be improved by intensification or extensification, this research would also provide any recommendations for efforts that could be done by the Government of Semarang in the intensification or extensification of regional taxes and levies area.The data required for this study were collected by using observation, interview, and documentation. Through these three techniques, research results were expected to be more objective or capable of describing the situation as it was. Primary data was done by conducting interviews with the competent parties to the topic under study for example the Head of Financial Management of Semarang or with the Head Office in connection with the management of regional taxes and levies in the city of Semarang.While the secondary data used in this analysis was the realization of Semarang city budget data of 2001 – the year 2006. In addition, also be taken aggregate data from the Office of Financial management (DPKD) City of Hyderabad as well as data from other agencies that had anything to do with local taxes in the city of Semarang.Tax Research showed street lighting was the largest contributor in the local tax penermaan Semarang city which is about 52.9 % in 2006. While the tax contributor to the smallest was the Tax Collection and Processing of Mineral C which was equal to 0.07 % in 2006. Viewed from the potential tax, objects and actually there were many taxprayers who had not managed entirely as expected from the regional regulation that govern, for example : Amusement Tax, Advertisement tax. While category C minerals tax and parking tax were still less than optimal in the collection, this was because in addition to taxprayer data difficult to quantify in real also very difficult to expect the mechanism of voting by self-payment.